Social rights and the politics of obligation in history / edited by Steven L.B. Jensen, The Danish Institute for Human Rights, Charles Walton, University of Warwick. - Jensen, Steven L. B., 1973-; Walton, G. Charles (George Charles), 1966- (Human rights in history., 2022)
This pioneering volume explores the long-neglected history of social rights, from the Middle Ages to the present. It debunks the myth that social rights are 'second-generation rights' - rights that appeared after World War II as additions to a rights corpus stretching back to the Enlightenment. Not only do social rights stretch back that far; they arguably pre-date the Enlightenment. In tracing their long history across various global contexts, this volume reveals how debates over social rights have often turned on deeper struggles over social obligation - over determining who owes what to whom, morally and legally. In the modern period, these struggles have been intertwined with questions of freedom, democracy, equality and dignity. Many factors have shaped the history of social rights, from class, gender and race to religion, empire and capitalism. With incomparable chronological depth, geographical breadth and conceptual nuance, Social Rights and the Politics of Obligation in History sets an agenda for future histories of human rights.